Polar cap patch transportation beyond the classic scenario. Issue 9 (20th September 2016) - Zhang, Qing‐He; Moen, Jøran; Lockwood, Michael; McCrea, Ian; Zhang, Bei‐Chen; McWilliams, Kathryn A.; Zong, Qiu‐Gang; Zhang, Shun‐Rong; Ruohoniemi, J. Michael; Thomas, Evan G.; Dunlop, Malcolm W.; Liu, Rui‐Yuan; et al.
Abstract: We report the continuous monitoring of a polar cap patch, encompassing its creation, and a subsequent evolution that differs from the classic behavior. The patch was formed from the storm‐enhanced density plume, by segmentation associated with a subauroral polarization stream generated by a substorm. Its initial antisunward motion was halted due to a rapidly changing of interplanetary magnetic field (IMF) conditions from strong southward to strong eastward with weaker northward components, and the patch subsequently very slowly evolved behind the duskside of a lobe reverse convection cell in afternoon sectors, associated with high‐latitude lobe reconnection, much of it fading rapidly due to an enhancement of the ionization recombination rate. This differs from the classic scenario where polar cap patches are transported across the polar cap along the streamlines of twin‐cell convection pattern from day to night. This observation provides us new important insights into patch formation and control by the IMF, which has to be taken into account in F region transport models and space weather forecasts. Key Points: The patch was formed from SED by segmentation associated with a SAPS generated by a substorm Antisunward moving patch was halted and evolved in nonclassical way associated with high‐latitude reconnection during northward IMF Much of patch faded rapidly due to an enhancement of the ionization recombination rate